4-2(-3)=8+y

Simple and best practice solution for 4-2(-3)=8+y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-2(-3)=8+y equation:


Simplifying
4 + -2(-3) = 8 + y

Multiply -2 * -3
4 + 6 = 8 + y

Combine like terms: 4 + 6 = 10
10 = 8 + y

Solving
10 = 8 + y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
10 + -1y = 8 + y + -1y

Combine like terms: y + -1y = 0
10 + -1y = 8 + 0
10 + -1y = 8

Add '-10' to each side of the equation.
10 + -10 + -1y = 8 + -10

Combine like terms: 10 + -10 = 0
0 + -1y = 8 + -10
-1y = 8 + -10

Combine like terms: 8 + -10 = -2
-1y = -2

Divide each side by '-1'.
y = 2

Simplifying
y = 2

See similar equations:

| (3*x)+7=25 | | 41x=800 | | .5x+2.66x=x+26 | | 2a+a=42 | | 3s+5l=28.20 | | 5-7(4-3x)=0 | | 25x+30=65x+20 | | 2(18-3y)+y=11 | | 1/6=3/10-1/15x | | 3(j+4)=-2j-8 | | 9a+4=67 | | m/5-3=7 | | 36.47=7g+3.78 | | 16.3k+7.5k+19.2=-64.1 | | 2a+8a=100 | | 10r^2-13r=4x^2+5 | | 7-4(6x+3)=2 | | 7(x-2)-2=2x+5(-3+x) | | 8x-4=-15x+50 | | 3v-20=-8(v-3) | | 3y=26 | | -8-3(1-4n)=-1+7n | | 21-(x+7)=8x-4 | | -7(v+2)+4v+6=7v+7 | | 3x-42x-6=0 | | I/2=17-21 | | A+7b+a+6c= | | 5x+6x=35 | | v=18t+18 | | 4x-6=7x+12 | | f(x+6)=x^2-6x+4 | | 8d+4d+6d-6-2d=0 |

Equations solver categories